The Identity of Garut Transgenders in Social Media - Raturahmi, Leadya; Dinda Putri, Nadya; Fanaqi, Chotijah; Yatnosaputro, Rosanti U. D. S. (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2023)
The background of this research is the use of social media by transgenders in the Garut Regency, although the transgender issue is contradictory to Indonesian values. This qualitative research uses rational choice theory to analyze social media usage as an identity for transgenders in the Garut Regency. The data are collected through in-depth interviews, observation, and literature study. The results show that transgenders use social media as an associative interaction. It shows their identity by 'behaving gender' and expressing the 'sense of we' as Sundanese women.